2021
DOI: 10.1039/d1ta03501k
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Zn-ion adsorption in cross-linked N/P co-incorporated porous carbon nanosheets for the zinc-ion hybrid capacitor

Abstract: Zinc-ion hybrid capacitors (ZHC) combining many advantages of supercapacitors and batteries, are promising new type of energy storage devices. However, the bottleneck of low energy density and inferior cyclic stability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…33 Zhang and co-workers incorporated N and P heteroatoms to boost zinc-ion adsorption of cross-linked porous carbon NSs, and obtained high ZIHC electrochemical performance. 34 These studies also reveal the importance of electrode design for achieving desirable electrochemical performance. To further meet the flexibility requirement and achieve energy matching with energy harvesting devices, key challenges such as compatible device capacitance and operating voltage remain for ZIHCs, which play an essential role and are a research spot for future self-powered energy systems to power various electronics.…”
Section: Introductionmentioning
confidence: 97%
“…33 Zhang and co-workers incorporated N and P heteroatoms to boost zinc-ion adsorption of cross-linked porous carbon NSs, and obtained high ZIHC electrochemical performance. 34 These studies also reveal the importance of electrode design for achieving desirable electrochemical performance. To further meet the flexibility requirement and achieve energy matching with energy harvesting devices, key challenges such as compatible device capacitance and operating voltage remain for ZIHCs, which play an essential role and are a research spot for future self-powered energy systems to power various electronics.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the highest specific capacity (182.6 mA h g −1 ) was achieved of B 2 S 3 C at 0.1 A g −1 due to the synergistic effect of B and S co-doping, superior to those of some advanced devices. 33,34,39,42,46,47 The EIS spectra in Fig. 5(c) shows that the minimum R s value of B 2 S 3 C was 0.867 Ω and the R ct value of B 2 S 3 C was smaller compared to those of B 0 S 0 C, B 2 S 0 C and B 0 S 3 C, which suggested that a rapid electrochemical reaction occurred at the interface of the electrode/electrolyte.…”
Section: Resultsmentioning
confidence: 98%
“…3(e) were 90°, 78°, 85°, and 65°, indicating that B 2 S 0 C and B 2 S 3 C showed an enhanced wettability of the electrolyte at the interface in contrast to B 0 S 0 C and B 0 S 3 C. This can be assigned to the formed functional groups containing oxygen (BC x O x ) due to the doping of B into B 0 S 0 C, and further resulted in the Zn 2+ and SO 4 2− in the electrolyte were easily contact the electrode surface. 39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gradual deviation of CV and GCD curves represents an indication of the probable coexistence of pseudocapacitance. 37 It is noteworthy that compared with the N-PCNT cathode (Fig. 3c), the SN-PCNT based ZHC possesses a superior rate capability with specic capacities of 152.6, 120.3, 106.7, 95.0, 80.6, 69.5, 62.5, 55.6 and 44.5 mA h g À1 This journal is © The Royal Society of Chemistry 2022 at current densities of 0.2, 0.5, 1, 2, 5, 10, 15, 25 and 40 A g À1 , respectively.…”
Section: Resultsmentioning
confidence: 99%